Behavioral and Biochemical Variations in Unio tigridis After Exposure to Lead Nitrate - Hanna, Nihal S.; Shekha, Yahya A. (Iraqi Journal of Science, 2024)
This study was carried out with the freshwater mussel Unio tigridis exposed to lead nitrate. The samples of water and mussels were collected from Qandil water resources situated in Qandil village at 36° 37’ 39.55" north latitude and 44° 10’ 51.80" east longitude, and it is 322 meters above sea level. In January 2022, rivers and aquariums water were tested for temperature, pH, EC, TDS, DO, total alkalinity, total hardness, and calcium and magnesium ions. Studied organisms were exposed to variable concentrations of lead nitrate ranging from 0 to 900 ppm. The 96-h median lethal concentration (LC50) was measured and a comparison was made between the behavioural responses of the control and treatment groups. Also, the concentrations of lead in the experimental media, shell, and soft tissue of mussels were measured. A sample of mussels collected from aquarium was tested for biochemical markers, including acetylcholinesterase (AChE), Glutathione S-Transferase (GST), Catalase (CAT) and malondialdehyde (MDA). After 96 hours, the LC50 was estimated to be 782.7 ppm. The findings on behaviours revealed that lead slows down species’ activities. Lead concentratiom increased within the mussel body as the water lead level decreased. The value of AChE was inversely related to lead concentration. However, GST, CAT and MDA increased with lead exposure.